A STUDY OF ADLER’S PERSONALITY THEORY IN CHRIS GARDNER’S CHARACTER IN THE PURSUIT OF HAPPYNESS MOVIE - APRIYANSYAH, VEGI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords: inferiority, superiority, Adler’s personality theory It can not be denied that within every individual there is feeling that can not be avoided. This feeling can lead us to be successful person or even be people who are desperate and sinking. That feeling is called inferiority by Adler. Referring to this, the writer undertook a study of Adler’s personality theory in Chris Gardner character in The Pursuit of Happyness movie. This film is based on true story of Chris Gardner who succesfully fought to achieve his superiority or in the other words became a successful person in his life. That is why in this study, the writer will answer the problem formulation that is: what are the influential factors within Chris Gardner’s personality to be successfull person in his life viewed from Adler's personality theory in “The Pursuit of Happyness” movie. This study used a qualitative approach to describe some of the factors that influential within Chris Gardner’s personality. The result of this study suggests that the success achieved by Chris Gardner is the result of a boost in his self to get out of the problems he faced and he wanted his son to know who his father is. From this case, Chris tried to compensate his inferiority and strive to achieve his superiority. Supported by fictional goal, conscious self, creative self, style of life and social interest all of which is inside Chris and supporting each other, so that made him become an expert in his job. Therefore he can be maximum in doing his job to become a stockbroker until eventually he achieve superiority or his success. The writer suggested the reader to understoodAdler's personality theory then applied in daily life to achieve the superiority. Moreover, the writer also suggested the further researchers to develope analysis from the other side, for example from the cultural, social, motivational or to compare it with another work.